2004
DOI: 10.1074/jbc.m407628200
|View full text |Cite
|
Sign up to set email alerts
|

The Pleckstrin Homology Domain of CK2 Interacting Protein-1 Is Required for Interactions and Recruitment of Protein Kinase CK2 to the Plasma Membrane

Abstract: CKIP-1 is a recently identified interaction partner of protein kinase CK2 with a number of protein-protein interaction motifs, including an N-terminal pleckstrin homology domain. To test the hypothesis that CKIP-1 has a role in targeting CK2 to specific locations, we examined the effects of CKIP-1 on the localization of CK2. These studies demonstrated that CKIP-1 can recruit CK2 to the plasma membrane. Furthermore, the pleckstrin homology domain of CKIP-1 was found to be required for interactions with CK2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 74 publications
3
60
0
Order By: Relevance
“…CKIP-1 was originally identified as a CK2␣-interacting protein. However, it has not been demonstrated whether CKIP-1 is involved in phosphorylation of CK2 substrates (18,19,23). Our data show for the first time that CKIP-1 delivers CK2␣ to PAK1 in response to EGF, and that this process is regulated by PI3K, demonstrating a mechanistic link between CK2 and PI3K signaling.…”
Section: Pi3k Regulation Of Pak1mentioning
confidence: 59%
See 2 more Smart Citations
“…CKIP-1 was originally identified as a CK2␣-interacting protein. However, it has not been demonstrated whether CKIP-1 is involved in phosphorylation of CK2 substrates (18,19,23). Our data show for the first time that CKIP-1 delivers CK2␣ to PAK1 in response to EGF, and that this process is regulated by PI3K, demonstrating a mechanistic link between CK2 and PI3K signaling.…”
Section: Pi3k Regulation Of Pak1mentioning
confidence: 59%
“…CKIP-1 exhibits a very broad spectrum of binding to phosphoinositols through its PH domain (19). In myoblast C2C12 cells, CKIP-1 binds to PI3P (phosphoinositol-3-phosphate) at the plasma membrane in response to insulin and regulates muscle differentiation; however, PI3K inhibition or coexpression of PI3K (⌬p85), a dominant negative mutant of PI3K, leads to nuclear accumulation of CKIP-1 (24).…”
Section: Pi3k Regulation Of Pak1mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this domain is necessary for interactions with protein kinase CK2, because mutants lacking the PH domain fail to interact with the kinase. Additionally, we have demonstrated that a subpopulation of protein kinase CK2 is targeted to the plasma membrane by CKIP-1 in cells (2). This targeting of CK2 is lost when the PH domain of CKIP-1 is replaced by a myristoylation recognition sequence, even though the CKIP-1 mutant still localizes to the plasma membrane.…”
mentioning
confidence: 92%
“…The cDNA for CKIP-1 codes for a protein of ϳ46 kDa with an amino-terminal pleckstrin homology (PH) domain and a carboxyl-terminal leucine-rich region as well as five putative PXXP motifs. The PH domain of CKIP-1 is required for phospholipid binding in vitro and for plasma membrane localization in cells (1,2). Furthermore, this domain is necessary for interactions with protein kinase CK2, because mutants lacking the PH domain fail to interact with the kinase.…”
mentioning
confidence: 99%